Desenvolvimento de uma ferramenta computacional aplicada na simulação de processos industriais - Felipe, Thiago do Amaral (2014)
The use of simulation in industrial environments allows the user to perform tests and define applied control strategies to cases where the network configuration, tuning the loop of control and the study of the timing constraints on the control can be evaluated before the implementation in the real plant. In this context there is the need to be developed simulated industrial networks, systems modeling interfaces protocols and possible integration with physical sensors available. This work presents a tool for real time simulation of an industrial process and data exchange with a server via Modbus protocol. That data can be viewed and manipulated by a supervisory system.